Hepatic veno-occlusive disease in children after hematopoietic stem cell transplantation - Mahadeo, Kris M. (J Pediatr Intensive Care, 2014)
Hepatic veno-occlusive disease (VOD), or sinusoidal obstruction syndrome, is a potentially fatal complication, which occurs in 7–27% of children undergoing hematopoietic stem cell transplantation. In this article, we review commonly accepted diagnostic criteria, atypical diagnostic features as well as preventative and treatment measures associated with VOD. Reversal of portal venous flow by Doppler ultrasound is often a late finding; many patients with anicteric VOD may never develop hyperbilirubinemia, and yet perish from severe VOD. Transjugular liver biopsy is usually not available and/or is often avoided. Prophylactic therapies with ursodeoxycholic acid, heparin and defibrotide are discussed. Supportive care with fluid restriction and diuretic therapy, analgesia, blood and platelet transfusions, paracentesis as well as other pulmonary and renal therapies remain imperative to superior outcomes. Specific therapy with thrombolytics such as defibrotide and recombinant tissue plasminogen activator is discussed and a classification of severity of VOD is proposed.